Study Protocol: Evaluating the Effect of Autologous Platelet-Rich Plasma Infusion in the Endometrial Cavity for Enhanced Embryo-Endometrium Synchrony in Patients with Repeated Implantation Failure - Sanket Mahajan; Akash More; Namrata Anjankar; Neha Varma; Neha Nawale (Journal of Pharmacy and Bioallied Sciences)
Background: Repeated implantation failure (RIF) is a significant challenge in IVF treatment, often related to insufficient endometrial thickness and poor embryo-endometrium synchrony. Platelet-rich plasma (PRP) therapy has shown promise in various medical fields but is under-explored in gynecology. This study aims to evaluate the effectiveness of PRP therapy in improving endometrial thickness and enhancing embryo-endometrium synchrony in women with RIF undergoing IVF. Objectives: The primary objective is to assess whether PRP therapy improves pregnancy outcomes, endometrial thickness, and embryo implantation rates in women with repeated implantation failure. Secondary objectives include comparing PRP therapy’s effectiveness to traditional IVF without PRP and establishing a standardized protocol for PRP preparation in clinical practice. Methodology: This prospective, randomized, controlled trial involved 100 women with a history of repeated implantation failure and thin endometrium. Participants were randomly assigned to two groups: an intervention group (n = 50) receiving autologous PRP therapy and a control group (n = 50) receiving IVF without PRP. PRP was prepared using a two-step centrifugation process. Endometrial thickness, embryo implantation rates, and pregnancy outcomes were compared between the two groups. Statistical analysis was performed using SPSS or R, with descriptive statistics, Chi-square tests, and t-tests. Expected Results: It is anticipated that the PRP therapy group will exhibit improved endometrial thickness, higher embryo implantation rates, and better pregnancy outcomes compared to the control group. Additionally, successful embryo transfers and live birth rates are expected to increase in the PRP-treated group. Study Implications: This study could provide valuable insights into the role of PRP therapy in enhancing IVF success rates for women with RIF, potentially offering a novel therapeutic approach in fertility treatments.